The role of values-based leadership in improving the teachers’ performance in public schools in Jeddah province - Al-Shamrani, Hilale Ahmed Abdullah (Journal of Educational and Psychological Sciences, 2021)
The aim of this research is to identify the degree of values-based leadership practice of educational leaders which contributes to raising the performance of teachers in public education schools in Jeddah from the point of view of teachers. In addition, in order to study the differences of the estimated means for the selective research group. Furthermore, it also aims to achieve the objectives of the research, it was used in terms of the implementation of leadership values to raise up the performance of academic female-staff regarding the variable of location of the educational office. The analytical descriptive approach was use to achieve the prospective target, survey has been utilized by focusing on how to apply the meaning of values-based leadership that consist of (32) concepts distributed on three different aspects, and was also applied on a sample of teachers who are working in public schools education,reached (865) teachers in the city of Jeddah, the second semester of the academic year 2019/1440. The results demonstrate that the degree of practice of the leaders of public education schools in Jeddah to manage the values from the point of view of the teachers came at a high level. The results also showed that there are statistically significant differences according to the location of the educational office in favor of Southern education office. The research presented several recommendations, the most important of which are: to promote the concept of management by values as a modern direction in administration for school leaders through conducting training courses under the supervision of specialists from the Ministry of Education, and expanding the contribution base of teachers in making administrative decisions related to the school.